PROMOSI MELALUI INSTAGRAM TERHADAP PENINGKATAN PENJUALAN - Hanggondosari, Sri Utami (Universitas Pawyatan Daha, 2023)
Marketing management is the art and science of selecting target markets and attracting, retaining, and growing customers by creating, delivering, and communicating superior customer value. This study aims to analyse the level of sales and customer relations, and describe the implementation of promotional activities. The results showed that the effect of promotion through Instagram is the increase in sales of IndiHome service products. In terms of promotion through Instagram media, it results in increased sales. The implementation of promotional activities through Instagram affects good relationships with customers. And from the calculation of the correlation in sales is 0.995 or 9.5%.